The Rationality of Indonesia Free-Active Politics Facing Chinese Aggressiveness in the Claims of the North Natuna Sea - Ma'ruf, Faridh; Tri Legionosuko,; Helda Risman, (Technium Social Sciences Journal, 2020)
China's claim to the North Natuna Sea is a manifestation of the South China Sea conflict. For this action, Indonesia responded with diplomatic rebuff either through political means or the presence of national defense and security stakeholders in the North Natuna Sea. The Chinese government responded that the claim of the Nine-dash Line that intersects with the North Natuna Sea EEZ is legal. This aggressive action of China is a threat to Indonesia's sovereign rights over the North Natuna Sea. This paper analyzes foreign policy as the political position of Indonesian interaction in responding to Chinese aggressiveness. The author uses descriptive analytical qualitative research methods using the Hedging Strategy and Dependency theory. The Chinese claim is a potential challenge to the interests and sovereignty of Indonesia, which is contested with the principle of a free and active foreign policy based on soft diplomacy and independent approach. The approach and steps of Indonesian politics become relevant if faced with conditions of asymmetrical power and Indonesia's National interest in China. So that Indonesia needs to build a more flexible foreign policy by maneuvering to emphasize China's aggressive attitude either directly or indirectly through hedging strategies.